Searching for the Least Invasive Management of Pelvi-Ureteric Junction Obstruction in Children: A Critical Literature Review of Comparative Outcomes - Marco Castagnetti; Massimo Iafrate; Ciro Esposito; Ramnath Subramaniam; Ramnath Subramaniam (Frontiers Media S.A., 2020)
Introduction: To review the published evidence on the minimally invasive pyeloplasty techniques available currently with particular emphasis on the comparative data about the various minimally invasive alternatives to treat pelvi-ureteric junction obstruction and gauge if one should be favored under certain circumstances.Materials and Methods: Non-systematic review of literature on open and minimally invasive pyeloplasty including various kinds of laparoscopic procedures, the robotic-assisted laparoscopic pyeloplasty, and endourological procedures.Results: Any particular minimally invasive pyeloplasty procedure seems feasible in experienced hands, irrespective of age including infants. Comparative data suggest that the robotic-assisted procedure has gained wider acceptance mainly because it is ergonomically more suited to surgeon well-being and facilitates advanced skills with dexterity thanks to 7 degrees of freedom. However, costs remain the major drawback of robotic surgery. In young children and infants, instead, open surgery can be performed via a relatively small incision and quicker time frame.Conclusions: The best approach for pyeloplasty is still a matter of debate. The robotic approach has gained increasing acceptance over the last years with major advantages of the surgeon well-being and ergonomics and the ease of suturing. Evidence, however, may favor the use of open surgery in infancy.